Prototype Android Application for Electromechanical Dimensioning of Glass Insulator Strings under IEC-60071 and IEC-60815 (2008) Standards - Millan Montalvo, Fabrizio Armando (2024)
In this study, a new Android application was developed to help users accurately determine the dimensioning of a string insulator through the analysis of the evaluation of two methods based on IEC-60071 and IEC-60815 (2008) standards. The first method uses equations from IEC-60815-2 (2008), while the second method considers parameters such as relative air density and pressure. To ensure reliability, both methods are evaluated: the first through the creepage factor to determine if the chosen profile is suitable, and the second through lightning and switching critical flashover voltages to avoid insulator flashover. Tests were carried out using data from real projects, and those results were compared with the results obtained from the application. The number of string insulators obtained from the tests was exactly the same as the number obtained from the application, except in two cases. Of the three evaluations, all cases complied satisfactorily with at least two tests.